Waste management in three public hospitals of Mato Grosso do Sul, Brazil - doi:10.5020/18061230.2010.p221 - Keila Tivirolli; Soraia Cristina Tivirolli; Patrícia Corrêa da Luz; Luana Barbiero Vieira Fujino; Marjolly Priscilla Shinzato; Josué Skowronski; Ariel Ortiz Gomes; Lúcia Helena de Andrade Vasconcelos; Sônia Corina Hess (Universidade de Fortaleza, 2012)
Objectives: To assess the management of health service waste generated in three public hospitals of Mato Grosso do Sul (Brazil), including qualitative and quantitative parameters. Methods: This was an observational and descriptive study. We assessed the waste management in two large public hospitals (HG1, 240 hospital beds and HG2, 343 beds) and in a small sized one (HP, 35 hospital beds). The data were collected in situ, by direct observation of the procedures for waste management and by quantifying the mass of waste generated by working sector in the three hospitals. Results: The study revealed that the internal management of waste generated in the three health care unities was not adequate, and that their workers were not trained on the proper management of waste and the use of personal protective equipment. The average rates of waste generation determined in HG1, HG2 and HP were, respectively, 4.7, 4.8 and 2.4 Kg.hospital bed-1.day-1, that fit the range of values reported in the literature. Conclusion: The detected inadequacies directly put at risk the health of workers and others who attend the three assessed hospitals and the outside comunity, which may be exposed to pathogens or toxic agents present in such waste.